Wound Healing Process of hemisection Lower Right 1st Molar Tooth After Administration of Silver Ion Water - Sukaton; Nirawati Pribadi; Nurfahira Paidal; Bernadus Daniel (Conservative Dentistry Journal, 2022)
Background. Hemisection Is a procedure for amputation of roots and resection of teeth performed due to periodontal abnormalities involving bifurcation, abnormalities in one root, very deep gingival margin due to caries or fracture. Tooth extraction is a process of alveolar dental expenditure , where the teeth are no longer able to do the treatment again . After the extraction of one of the roots the tooth socket heals slowly. Some factors such as lack of blood supply, dehydration, exudate excess, or foreign bodies hamper socket healing. Silver Ion Water is liquid embedded with silver ion which is known to promote wound healing. This study utilizes silver ion water of 15 ppm concentrate. Purpose. To understand the process of wound healing after 1 root tooth extraction the water supply of silver ions Method. Marmot teeth removed , then the wound was given H2O2 for 3 days to make chronic inflammation . Samples were divided into 3 groups . Wounds of the control group were not given water silver ions , group 1 was given a silver ions water for 3 days , group 2 was given a silver ion water for 5 days . On day 8 , the socket is cut and fabricated plate HPA .Results . The number of fibroblasts , chronic inflammatory cells , blood vessels of the control group was 64 , 97 , 22 , group 1 was 84 , 78 , 31 , group 2 was 119 , 40 , 45 .Conclusion . Silver Ion Water shown to accelerate wound healing after one root extraction .